(untitled) (Journal of Asian Geography, 2024)
Geotourism is a niche market that contributes to sustaining and even enhancing the geographical characteristics of a territory, including the abiotic, biotic, and cultural (ABC) attributes of destinations. It uplifts the living standards of local communities and provides opportunities for visitors to understand and appreciate the natural environment and the existing culture of the geosites. The aim of this research was to evaluate the geotourism characteristics of the Hummanaya tourism destination based on stakeholders’ opinions and to investigate the extent to which stakeholders are committed to adhering to geotourism principles. Primary and secondary data sources were utilized to collect the necessary data for this study. For gathering primary data, key informant interviews and participatory observations were conducted in the field using a semi-structured questionnaire, with purposive sampling employed. Unpublished documents served as secondary data. Descriptive statistical analysis and narrative interpretation methods were used to analyze the collected data. The study was able to identify the extent to which geotourism stakeholders adhere to geotourism principles. Specifically, regarding the principles of integrity, community involvement, community benefits, and tourist satisfaction, the informants provided positive responses. The findings reveal that the destination is perceived by tourists as a fascinating and unique tourist attraction in Sri Lanka. Most tourists reported being very satisfied or satisfied with the tourist attractions, facilities, and services provided by local facilitators, indicating that the destination meets tourists’ expectations. However, a significant issue is whether other stakeholders are satisfied with geotourism's contributions to protecting the destination's ABC attributes and improving the socio-economic status of local communities. Negative responses were noted concerning principles such as evolution, market selectivity, interactive interpretation, and market diversity. Therefore, necessary measures must be taken to conserve and develop the destination as a geosite and geotourism site.